2004
DOI: 10.1162/15353500200403172
|View full text |Cite
|
Sign up to set email alerts
|

Validating Bioluminescence Imaging as a High-Throughput, Quantitative Modality for Assessing Tumor Burden

Abstract: Bioluminescence imaging (BLI) is a highly sensitive tool for visualizing tumors, neoplastic development, metastatic spread, and response to therapy. Although BLI has engendered much excitement due to its apparent simplicity and ease of implementation, few rigorous studies have been presented to validate the measurements. Here, we characterize the nature of bioluminescence output from mice bearing subcutaneous luciferase-expressing tumors over a 4-week period. Following intraperitoneal or direct intratumoral ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 18 publications
6
37
0
Order By: Relevance
“…Signal is attenuated at depth, but the technique can be applied routinely in both SC models and for monitoring orthotopic tumor development (3)(4)(5)(6)(7)(8)12 Author Manuscript calipers or MRI (5,12,38,39). In our early work we found strong correlations (r>0.8) between peak light signal, initial area under the curve, or signal intensity at 10 minutes post luciferin infusion and tumor volume following IP administration of 150 mg/kg D-luciferin (12). However individual measurements showed discrepancies and consecutive observations could vary by as much as 60%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal is attenuated at depth, but the technique can be applied routinely in both SC models and for monitoring orthotopic tumor development (3)(4)(5)(6)(7)(8)12 Author Manuscript calipers or MRI (5,12,38,39). In our early work we found strong correlations (r>0.8) between peak light signal, initial area under the curve, or signal intensity at 10 minutes post luciferin infusion and tumor volume following IP administration of 150 mg/kg D-luciferin (12). However individual measurements showed discrepancies and consecutive observations could vary by as much as 60%.…”
Section: Discussionmentioning
confidence: 99%
“…Bioluminescence imaging has also found widespread use in examining changes in tumor growth over a period of many weeks with diverse therapies (6)(7)(8)(9)(10). Bioluminescent imaging requires administration of luciferin substrate, which may be achieved by multiple routes including intravenous (IV), intra peritoneal (IP) or subcutaneous (SC) (11,12). Luciferin is then carried throughout the vasculature and has been shown to readily permeate every region of the body (9,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Bioluminescence imaging (BLI), especially, demonstrates the most desirable combination of high sensitivity and easy handling (5) and is suitable for acquire signal deep in tissue (6). It has been widely used for monitoring different cancer biological processes [angiogenesis (7,8), infinite proliferation and meta stasis (9,10), multidrug resistance (11,12)] and assessing the efficacy of different therapeutic modalities (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue particularly attenuates light with a wavelength in the range of 400 to 600nm, but less between 600 to 950nm [192]. Indeed, we observed that (pigmented) hair and skin absorbed much light, as reported [193]. In principle, the light intensity is attenuated approximately 10-fold for every centimetre of tissue depth [194].…”
Section: Discussionsupporting
confidence: 79%